Assessment of carbon monoxide levels at signalized intersection and roadway - Kho, Freddy Wee Liang (Universiti Malaysia Sarawak, UNIMAS, 2008)
An assessment of carbon monoxide (CO) levels had been carried out using CAL3QHC air dispersion model in simulating the aerial variation of 1-hr averaged CO levels at 1) Mabel Signalized Intersection, Kuching, and 2) Sembulan Roadway, Kota Kinabalu. Field measurements on CO levels at hot-spots during typical peak hours had successfully been conducted at the identified study areas. Based on the results, the CO levels at the Mabel Signalized Intersection and Sembulan Roadway did not pose any significant impacts on road sites and nearby population of the areas under study, Even though the present study had shown no alarming situation with regard to CO levels, the receptors located near to the intersection and roadway have the potential risk of being exposed to marginally higher levels of CO in a long-term.